Analysis of Junior High School Students' Ability to Understand Mathematical Concepts in Statistics Materials Reviewed from Gender - Bara, Muhammad Ilham Maulana Batu; Afri, Lisa Dwi (SAINTIS Publishing, 2024)
Male students are different from women in acquiring, understanding and mastering mathematical concepts. This study intends to describe the ability of students to understand mathematical concepts from a gender perspective. The ability to understand mathematical concepts is analyzed from problem solving. This study applies a qualitative descriptive method. The subjects of the study were male and female students in grade IX of the Medan National Hero Private Junior High School as many as 12 people each. The research instrument used was in the form of a written test of mathematical concept comprehension ability consisting of 3 valid essay questions and an interview. The data was analyzed based on gender indicators of mathematical concept comprehension ability, namely restating concepts that have been learned, using certain procedures or operations, and applying concepts in meaningful problem solving to the concepts studied. Data are compared by gender. The results of the study showed that the ability to understand mathematical concepts of female students was better than that of male students on the indicators of restating the concepts that had been learned, using certain procedures or operations and applying concepts in meaningful problem solving to the concepts studied, which can be seen from the average achievement of female students 72.183 while male students reached an average of 58.3.